2021
DOI: 10.1111/oik.08677
|View full text |Cite
|
Sign up to set email alerts
|

Clumpy coexistence in phytoplankton: the role of functional similarity in community assembly

Abstract: Emergent neutrality (EN) suggests that species must be sufficiently similar or sufficiently different in their niches to avoid interspecific competition. Such a scenario results in a transient pattern with clumps and gaps of species abundance along the niche axis (e.g. represented by body size). From this perspective, clumps are groups of coexisting species with negligible fitness differences and stochastic abundance fluctuations. Plankton is an excellent model system for developing and testing ecological the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…number of clusters and within cluster richness) are often very similar between prey and predator communities and can be strongly interrelated (Figure S3a,b). So far, empirical proofs of clusters with similar species have only been reported from a competition perspective focusing on single communities and only originating from field data (D'Andrea et al, 2020; Graco‐Roza et al, 2021; Scheffer & van Nes, 2006; Segura et al, 2011). We lack proof of niche clusters among prey and their predators from both nature and experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…number of clusters and within cluster richness) are often very similar between prey and predator communities and can be strongly interrelated (Figure S3a,b). So far, empirical proofs of clusters with similar species have only been reported from a competition perspective focusing on single communities and only originating from field data (D'Andrea et al, 2020; Graco‐Roza et al, 2021; Scheffer & van Nes, 2006; Segura et al, 2011). We lack proof of niche clusters among prey and their predators from both nature and experiments.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of empirical studies report such clustering patterns along trait axes, which can be seen as surrogates of the niche axis (D'Andrea et al, 2020; Segura et al, 2011, 2013; Vergnon et al, 2009, 2012). For instance, clusters have been detected in the distribution of tree height and wood density in tropical forests (D'Andrea et al, 2020), in the size distribution of marine and freshwater phytoplankton (Graco‐Roza et al, 2021; Segura et al, 2011, 2013) or aquatic beetles (Scheffer et al, 2015). While various mechanisms have been shown to promote the emergence of niche clustering and its stability over time (D'Andrea et al, 2019; Sakavara et al, 2018; Scheffer & van Nes, 2006), all the mechanisms studied so far still rely on competition among species.…”
Section: Introductionmentioning
confidence: 99%
“…More recent numerical simulations of the dynamics of the species-reach Lotka-Volterra community with interspecific competition quantified by niches overlap have indeed shown a lumpy distribution of species along a niche axis 13 , which actually confirms May's rather general surmise in a particular embodiment. We hypothesize that this is the case with phytoplankton communities, the more so because there are empirical evidences 14,15,16 to support this.…”
mentioning
confidence: 87%
“…We hypothesize that this is also the case with phytoplankton communities, all the more so because there are empirical evidences to support this (Vergnon et al 2009). Indeed, drawing on the correlations between morphological properties and functional traits of phytoplankton species (Kruk and Segura 2012), a number of studies (Segura et al 2011(Segura et al , 2013Graco-Roza et al 2021) have suggested that the multimodal pattern observed in species size distribution within phytoplankton communities reflects a clustered arrangement of species along niche gradients.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Common narratives include the idea that complexity is typical of systems composed of multiple, diverse parts and structured across different organizational levels ( 3 – 5 , 18 , 21 , 33 ), a vision that puts networks ( 53 , 65 ) and hierarchies ( 9 , 66 , 67 ) at the core of ecological complexity. Other concepts include spatiotemporal scale dependencies ( 28 , 68 70 ), criticality ( 11 , 71 ), self-organization of the parts that compose a system in increasingly sophisticated modules ( 9 , 21 , 33 , 72 , 73 ), and feedbacks occurring both within and between each level of the system, which stabilize and constrain both the whole system and its parts ( 6 , 18 , 31 , 68 , 70 ). Chaotic dynamics and the potential for alternative states, which are often contingent on the initial conditions of a system and may operate at any organizational level, complete the typical recipe of a complex system ( 2 , 18 , 74 , 75 ).…”
Section: Untangling the Fabric Of Ecological Complexitymentioning
confidence: 99%